2011
DOI: 10.4209/aaqr.2011.02.0016
|View full text |Cite
|
Sign up to set email alerts
|

Indoor PM2.5 Characteristics and CO Concentration Related to Water-Based and Oil-Based Cooking Emissions Using a Gas Stove

Abstract: Pollutant emissions from indoor cooking activities using clean fuels such as natural gas or LPG are strongly influenced by cooking ingredients and cooking methods. In this study, we explore the characterization of indoor fine particles (PM 2.5 ) and CO that are produced by two distinctive cooking methods: frying and boiling. This characterization includes quantifying the presence of fine particles in a kitchen as well as in the adjoining room, analyzing size-segregated carbonaceous materials (EC and OC), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…PM concentrations rise and fall sharply while concentrations of CO show a gradual increase and decrease around the peaks of CO. Depending on the cooking method, PM emissions can vary significantly (Huboyo et al, 2011). Ezzati et al (2000) also observed this trend of sharper fluctuations of PM 10 with respect to CO in Kenya, explaining his wide range of correlation (r 2 = 0.14 -0.91) between the two parameters.…”
Section: Co To Pm 25 Correlationmentioning
confidence: 84%
“…PM concentrations rise and fall sharply while concentrations of CO show a gradual increase and decrease around the peaks of CO. Depending on the cooking method, PM emissions can vary significantly (Huboyo et al, 2011). Ezzati et al (2000) also observed this trend of sharper fluctuations of PM 10 with respect to CO in Kenya, explaining his wide range of correlation (r 2 = 0.14 -0.91) between the two parameters.…”
Section: Co To Pm 25 Correlationmentioning
confidence: 84%
“…There is growing public awareness regarding health risks associated with poor indoor air quality (Huboyo et al 2011;Hulin et al 2012; World Health Organization (WHO) 2010). Because people spend majority of their time indoors (Klepeis et al 2001), they are at greater risk of adverse health effects from chronic exposures to indoor air pollutants (Bernstein et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to investigate airborne particulate matter and metals in workplaces, urban and rural area (Begum et al, 2010;Shen et al, 2010;Choosong et al, 2010;Huboyo et al, 2011;Ny and Lee, 2011;Tsai et al, 2011). However, investigations into airborne asbestos concentrations in rural areas containing natural asbestos outcrops are rare.…”
Section: Introductionmentioning
confidence: 99%